A genomic mutation spectrum of collecting duct carcinoma in the Chinese population - Huaru Zhang; Xiaojun Lu; Gang Huang; Meimian Hua; Wenhui Zhang; Tao Wang; Liqun Huang; Ziwei Wang; Qing Chen; Jing Li; Qing Yang; Guosheng Yang (BMC, 2022)
Abstract Background Renal collecting duct carcinoma (CDC) is a rare and lethal subtype of renal cell carcinoma (RCC). The genomic profile of the Chinese population with CDC remains unclear. In addition, clinical treatments are contradictory. In this study, we aimed to identify the genomic mutation spectrum of CDC in the Chinese population. Methods Whole-exome sequencing was performed using the Illumina Novaseq™ 6000 platform. MuTect2 detects single-nucleotide variants (SNVs) and small scale insertions/deletions (INDELs). The identified mutations were annotated with ANNOVAR and validated by Sanger sequencing. Control-FREEC was used to detect copy number variation (CNV), and GISTIC was applied to detect frequently mutated altered regions. These data were compared with associated The Cancer Genome Atlas cohorts. Results Ten normal-matched CDC patients were included. The mean tumour mutation burden was 1.37 Mut/Mb. Six new recurrent somatic mutated genes were identified, including RBM14, MTUS1, GAK, DST, RNF213 and XIRP2 (20% and 2 of 10, respectively), and validated by Sanger sequencing. In terms of common mutated genes, SETD2 was altered in both CDC and other RCC subtypes but not in bladder urothelial carcinoma (BLCA); CDKN2A was a driver gene in both CDC (SNV: 10%, 1 of 10) and BLCA but not in other RCC subtypes. Next, 29 amplifications and 6 deletions of recurrent focal somatic CNVs were identified by GISTIC2.0, which displayed differences from kidney renal clear cell carcinoma (KIRC), kidney renal papillary cell carcinoma (KIRP) and BLCA cohorts. Of note, CDKN2A (CNV alteration: 30%, 3 of 10) and CDKN2A-AS1 were the only overlapping genes of these four cohorts. Importantly, the CDKN2A mutation in our cohort differed from previous studies in urinary carcinomas. Moreover, CDKN2A-altered cases had significantly worse overall survival than wild-type cases in both KIRC and KIRP cohorts. In addition, the most frequently altered genomic pathway of our CDC cohort was the CDKN2A-mediated p53/RB1 pathway. Conclusions Our study offers the first genomic spectrum of the Chinese population with CDC, which differs from that of the Western population. The altered CDKN2A-mediated p53/RB1 pathway might provide new insight into potential therapeutic targets for CDC patients.